A digital advocate? Reactions of rural people who experience homelessness to the idea of recording clinical encounters. (7th September 2016) - Grande, Stuart W.; Castaldo, Mary Ganger; Carpenter‐Song, Elizabeth; Griesemer, Ida; Elwyn, Glyn
Abstract: Background: Are the benefits of recording clinical encounters shared across different groups, or do they vary based on social position? Studies show that educated patients record their clinical visits to enhance their experience, but very little is known about recording benefits among "hard‐to‐reach" populations. Objective: To examine the reactions of homeless people to the idea of using a smartphone to record their own clinical encounter, either covertly or with permission from their physician. Method: We conducted semi‐structured interviews with individuals at a temporary housing shelter in Northern New England. A thematic analysis identified themes that were iteratively refined into representative groups. Results: Eighteen (18) interviews were conducted, 12 with women and six with men. Initial reactions to clinical recordings were positive (11 of 18). A majority (17 of 18) were willing to use recordings in future visits. A thematic analysis characterized data in two ways: (i) by providing reliable evidence for review, they functioned as an advocacy measure for patients; (ii) by promoting transparency and levelling social distance, this technology modified clinical relationships. Discussion: Recordings permitted the sharing of data with others, providing tangible proof of behaviour and refuting misconceptions. Asking permission to record appeared to modify relationships and level perceived social distance with clinicians. Conclusions: We found that while many rural, disadvantaged individuals felt marginalized by the wide social distance between themselves and their clinicians, recording technology may serve as an advocate by holding both patients and doctors accountable and by permitting the burden of clinical proof to be shared.